2021
DOI: 10.5551/jat.60087
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of Precision Medicine for Atherosclerotic Cardiovascular Disease Based on Human Genome Information

Abstract: The official journal of the Japan Atherosclerosis Society and the Asian Pacific Society of Atherosclerosis and Vascular Diseases Review Precision or personalized medicine is currently gaining a lot of attention. Clinical evidence for its effectiveness has been established based on randomized clinical trials accounting for classical risk factors, such as hypertension, diabetes, and serum lipids. However, besides such classical risk factors, the genetic background should be considered, at least for heritable tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 51 publications
(48 reference statements)
0
6
0
1
Order By: Relevance
“…Thus, various genetic variants with unclear pathogenicity are identified. 17 18 This study proposed a useful scheme and identified the putative pathogenic variants of sitosterolemia, which can be helpful in genetic diagnosis in not only in Japan but also other countries worldwide. Notably, the scheme is reproducible anywhere, paving the way for further related research.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, various genetic variants with unclear pathogenicity are identified. 17 18 This study proposed a useful scheme and identified the putative pathogenic variants of sitosterolemia, which can be helpful in genetic diagnosis in not only in Japan but also other countries worldwide. Notably, the scheme is reproducible anywhere, paving the way for further related research.…”
Section: Discussionmentioning
confidence: 99%
“…Various genomics studies have been conducted recently to discover underlying genetic aetiology in CVD patients, especially those suspected of HF disease 47,48 . Several CVD‐related genes have significant mutations and expression differences among CVD patients 49–51 . To study chronic diseases with complex biological processes, it is imperative to take an integrative approach that combines multi‐omics data to highlight the intricacies associated with molecular functions.…”
Section: Introductionmentioning
confidence: 99%
“…47,48 Several CVD-related genes have significant mutations and expression differences among CVD patients. [49][50][51] To study chronic diseases with complex biological processes, it is imperative to take an integrative approach that combines multi-omics data to highlight the intricacies associated with molecular functions. In this study, we performed a multi-faceted approach involving WGS integrated with differential gene expression for HF and other CVD study.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic factors substantially affect the development of atherosclerotic cardiovascular disease 1) . In the previous decade, numerous studies actively investigated genetic variants contributing to this risk, finding that many of them are related to traditional clinical factors, whereas others are linked to noncoding genetic regions and uncertain pathways [2][3][4][5] .…”
Section: Introductionmentioning
confidence: 99%